2012
DOI: 10.1016/j.neuropharm.2012.08.011
|View full text |Cite
|
Sign up to set email alerts
|

Phenylpiperazine derivatives with selectivity for dopamine D3 receptors modulate cocaine self-administration in rats

Abstract: This study examined cocaine self-administration after pretreatments with three structurally related compounds that bind selectively to dopamine D3 receptors (D3Rs) relative to the D2 receptor subtype (D2Rs) and exhibit varying intrinsic activities in the forskolin-stimulated adenylyl cyclase assay. The compounds are: a) WC10, a D3R weak partial agonist/ antagonist with 42-fold D3R:D2R selectivity, b) WC26, a 51-fold selective D3R partial agonist, c) WC44, a 23-fold selective D3R agonist. Rats were stabilized o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
28
1

Year Published

2012
2012
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(32 citation statements)
references
References 77 publications
(115 reference statements)
3
28
1
Order By: Relevance
“…22,31 Development of D2 and D3 receptor subtype selective compounds would provide the pharmacological tools to enable the neuroscience community to better understand the role of these two receptor subtypes in complex behavioral and physiological processes. Furthermore, D2-like receptor subtype selective compounds of varying intrinsic activity have the potential for development of (a) pharmacotherapeutic agents for the treatment of neurological disorders, 6 neuropsychiatric disease, 32 and psychostimulant abuse, 33 and (b) neuroimaging agents to study the differential expression and regulation of D2-like dopamine receptors. 34,35 We initially assumed that ligand binding selectivity would be achieved by developing compounds capable of exploiting differences in contact residues between these two structurally related receptor subtypes.…”
Section: ■ Discussionmentioning
confidence: 99%
“…22,31 Development of D2 and D3 receptor subtype selective compounds would provide the pharmacological tools to enable the neuroscience community to better understand the role of these two receptor subtypes in complex behavioral and physiological processes. Furthermore, D2-like receptor subtype selective compounds of varying intrinsic activity have the potential for development of (a) pharmacotherapeutic agents for the treatment of neurological disorders, 6 neuropsychiatric disease, 32 and psychostimulant abuse, 33 and (b) neuroimaging agents to study the differential expression and regulation of D2-like dopamine receptors. 34,35 We initially assumed that ligand binding selectivity would be achieved by developing compounds capable of exploiting differences in contact residues between these two structurally related receptor subtypes.…”
Section: ■ Discussionmentioning
confidence: 99%
“…We found that three of these compounds-WC10, WC26, and WC44-reduced cocaine self-administration (Cheung et al, 2012). Although the response rate under sucrose reinforcement was also reduced, the latency to respond (i.e., the time between lever insertion and the first response on the active lever) increased as a function of dose for WC26 and WC44 when the reinforcer was cocaine but not when the reinforcer was sucrose.…”
Section: Introductionmentioning
confidence: 84%
“…Systemic cocaine, OS-3-106, WW-III-55, and their vehicles were given intraperitoneally, and 7-OH-DPAT and its vehicle were given subcutaneously. OS-3-106 and WW-III-55 were injected 5 minutes before the start of the test session, based on our previous study showing that arylamide phenylpiperazines attenuated L-DOPAinduced dyskinesia (Kumar et al, 2009) and reduced locomotor activity (Cheung et al, 2012) within this time frame.…”
Section: Evaluation Of the Effects Of Os-3-106 And Ww-iii-55 On Behaviormentioning
confidence: 99%
See 2 more Smart Citations